Chemokine receptor Ccr1 drives neutrophil-mediated kidney immunopathology and mortality in invasive candidiasis. - Michail S Lionakis; Brett G Fischer; Jean K Lim; Muthulekha Swamydas; Wuzhou Wan; Chyi-Chia Richard Lee; Jeffrey I Cohen; Phillip Scheinberg; Ji-Liang Gao; Philip M Murphy (PLoS Pathogens)
Invasive candidiasis is the 4(th) leading cause of nosocomial bloodstream infection in the US with mortality that exceeds 40% despite administration of antifungal therapy; neutropenia is a major risk factor for poor outcome after invasive candidiasis. In a fatal mouse model of invasive candidiasis that mimics human bloodstream-derived invasive candidiasis, the most highly infected organ is the kidney and neutrophils are the major cellular mediators of host defense; however, factors regulating neutrophil recruitment have not been previously defined. Here we show that mice lacking chemokine receptor Ccr1, which is widely expressed on leukocytes, had selectively impaired accumulation of neutrophils in the kidney limited to the late phase of the time course of the model; surprisingly, this was associated with improved renal function and survival without affecting tissue fungal burden. Consistent with this, neutrophils from wild-type mice in blood and kidney switched from Ccr1(lo) to Ccr1(high) at late time-points post-infection, when Ccr1 ligands were produced at high levels in the kidney and were chemotactic for kidney neutrophils ex vivo. Further, when a 1∶1 mixture of Ccr1(+/+) and Ccr1(-/-) donor neutrophils was adoptively transferred intravenously into Candida-infected Ccr1(+/+) recipient mice, neutrophil trafficking into the kidney was significantly skewed toward Ccr1(+/+) cells. Thus, neutrophil Ccr1 amplifies late renal immunopathology and increases mortality in invasive candidiasis by mediating excessive recruitment of neutrophils from the blood to the target organ.